Effective Evaluation Methods for Fractured Tight Sandstone Reservoirs in Kuqa Depression - LIU Shiwei; BIE Kang; WANG Dongdong; NI Xiaowei; LIU Min; XU Sihui; FENG Jiaming (Cejing jishu)
The multi-genetic fracture in Kuqa depression of Tarim basin provide effective reservoir space and permeability pathways for the reservoir, and the matrix rock blocks have small porosity, making it a typical fractured tight sandstone reservoir. Faced with the problems of low porosity and permeability, fine throats, poor connectivity, and strong heterogeneity in the deeply buried, complex tight sandstone reservoir, the effective reservoir evaluation is faced with uncertainty. In the case where the single well has similar petrophysical and fracture qualitative evaluation, the test production capacity is different, and there is an urgent need to conduct a well test evaluation research. By analyzing the factors affecting the quality of fractured tight sandstone reservoirs from the perspectives of porosity, fracture parameters, and stress, a systematic analysis and summary of the influencing factors is carried out. Selecting parameters such as porosity, fracture porosity, fracture width, and the angle between the maximum horizontal principal stress and the fracture strike direction, the sandstone reservoir quality is depicted using test data, and the reservoir quality is differentiated by adjusting the main control factor correlation coefficient. A reservoir quality factor is established, and a method of identifying reservoir effectiveness using reservoir quality factor is formed. This method has achieved good results in new well interpretation and evaluation, providing technical support for subsequent interpretation and evaluation.